Diabetic Patients Knowledge and Practice Regarding Annual Visual Checking - Mukhaiseer, Maha Hussein (AL-Kindy College Medical Journal, 2020)
Background: Diabetes mellitus (DM) is a significant cause of visual impairment; many diabetics do not have regular eye examinations, although it is known that early diagnosis and reduces the risk of blindness. There were many barriers that prevent diabetics from attending eye clinics.Objectives: To assess knowledge, and practice about ocular complications among diabetic patients and to determine barriers preventing the diabetic patients annual visual checkingMethods: A cross-sectional study involving the interview was conducted among 300 diabetic patients attending out patient in Ibn Al Haitham Teaching Ophthalmology Hospital between November 2017 and June 2018.Results: The vast majority of patients (95%) believe that; diabetes could affect their eyes. 67% have their eyes checked up after being diagnosed with diabetes, of which only 33% they examined their eyes if vision got poor. Majority of patients believe that; controlling their blood sugar levels can help preserve their vision (84%).  72% of the total has good knowledge of DM effect on the eye. 55% of patients obtained their knowledge from the doctor and only 2% having obtained this knowledge from Television. Unfortunately only 3% of them check their vision annually 37 % they don’t know treatments available for diabetic retinopathy.Conclusion: Diabetic patients’ knowledge of ocular manifestations and the practice of diabetic patients towards eye examination were low, thus required to improve practice towards eye care to prevent visual impairment.